An attempt to enhance solubility of metoclopramide base by Solid dispersion strategy and its application on development of Transdermal device - Nancy Kahali; Jasmina Khanam; Nondita Ghosh (Universidade de São Paulo, 2021)
Chemotherapy induced nausea and vomiting (CINV) is an issue, which usually occurs in cancer patient. Despite high bioavailability of oral and intravenous administration, these have some drawbacks. The oral route causes hepatic first pass metabolism and intravenous route is invasive in nature. Hence, antiemetic drug by means of transdermal route is necessary to administer in such cases. The aim of the present investigation is to develop suitable Transdermal Therapeutic System (TTS) with an objective to enhance solubility and skin permeability properties of metoclopramide base. Preformulation study begins with an approach to enhance solubility of 40 metoclopramide base by solid dispersion technique. transdermal films were prepared with 41 the solid dispersion as well as with pure drug. Phase solubility study at various temperatures reveals binding constants (Ka, 95-350 M-1 for PVP K30; 56-81 M-1 for HPβCD). Spontaneity of solubilization was justified by AL type linear profiles. The films showed satisfactory diffusion (%), permeation rate and flux after 8 h study. The transdermal patches as prepared were analyzed under FTIR, DSC and SEM. Both solubility and permeability rate in this investigation have been enhanced. So, it can be affirmed that this route would effectively enhance bioavailability